Housing Supply and Land Use Regulation in the Netherlands - Wouter Vermeulen; Jan Rouwendal (Tinbergen Institute, 2007)
In spite of a growing recognition of the importance of supply conditions for the level and volatility of house prices, empirical work on housing supply outside the US is scarce. This paper considers various measures of housing supply in the Netherlands, where real house prices have roughly tripled since 1970. Besides the volume of investment in residential structures, and new housing construction in units, we derive time series of structure and location quality in a hedonic analysis. Each of these variables appears to be almost fully inelastic with respect to house prices in at least the short to medium long run. Further analysis of the quality of location index shows that conventional models of competitive land and housing markets cannot account for these findings. However, they may be well explained in terms of the rather extensive body of interventions by the Dutch government.
Keywords: E22; R31; R52; 330; housing supply; residential investment; housing markets; land use regulation; Wohnungsmarkt; Angebot; Bauinvestition; Immobilienpreis; Bodennutzung; Raumordnungsrecht; Niederlande